Efektifitas Dalam Harta Bersama yang Diikat Oleh Perjanjian Pranikah - Utami, Tiara Hadiyatun; Badzli, Naia Putri; Adinda, Abelia Putri; Antika, Rindu; Chaerudin, Marchelia Naomi; Rasyad, Fabian; Faturahman, Dadan Taufik (Universitas Sains dan Teknologi Komputer, 2025)
Religious Courts are judicial institutions that examine, try and decide civil cases that apply to people who are Muslims, based on Islamic law and religious court procedural law. Religious Courts have special authority to handle civil cases related to Islamic law such as marriage, inheritance, wills, grants, waqf, zakat, infaq, etc. Especially in expiration. Especially inexpiration. The concept of expiration (verjaring) relates to the time limit for filing a claim or lawsuit, as well as the provision of time limits on a case that occurs. The main purpose of religious courts is to uphold justice for Muslims by applying applicable Islamic law. One of them is the existence of an open trial conducted in the Religious Courts, especially the Sumber Class IA Religious Court. One example is the trial of case number 995/Pdt.G/2025/PA.Sbr, namely about Joint Property or expiration conducted by Mr. Harsono as the Plaintiff and Mrs. Siti Aisyah as the Defendant. This research method uses Normative Juridical research or an approach in legal research that focuses on legal norms, laws and regulations, legal principles, and applicable legal doctrines. This approach examines how the law should be applied and how people should behave in the context of the law.